Implementation of Lesson Plan with Zone Proxima Development at MI Alam Ali Thaibah Cibitung Bekasi - Darmawati, Darmawati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
MI Alam Ali Thaibah is a formal school that employs the natural school curriculum as its primary curriculum. In the teaching and learning process, the natural school curriculum is integrated with the national curriculum. The concept of the natural school combines three pillars of education: faith, knowledge, and leadership, as reflected in the vision and mission of MI Alam Ali Thaibah. The school envisions producing leaders who are devout, knowledgeable, and possess noble character, becoming a source of blessing for the entire universe. The mission includes fostering students' awareness of their responsibilities as servants of Allah, creating an environment that upholds moral values, instilling religious habits, preparing students to be trustworthy leaders, providing basic entrepreneurship education for student independence, developing effective communication skills, honing emotional intelligence in interactions, facilitating students to acquire extensive knowledge, and instilling awareness of the importance of preserving the environment.implementation of ZPD Lesson Plan (RPP) in MI Alam Ali Thaibah in Cibitung - Bekasi.this research employed qualitative research, the result show that the target audience for this community service activity is the teachers of MI Alam Ali Thaibah in Cibitung - Bekasi. The presentation of community service material for these teachers includes lectures, demonstrations, and practical exercises with question and answer sessions. Lectures are used to explain introductory concepts and theories of teaching media, demonstrations illustrate the stages of creating RPP using the ZPD method, and question and answer sessions provide participants with the opportunity to consult on overcoming challenges in implementing teaching techniques.